Establishment and application of a TaqMan-based multiplex real-time PCR for simultaneous detection of three porcine diarrhea viruses - Ren, Jing; Zu, Congcong; Li, Yang; Li, Meng; Gu, Jinyuan; Chen, Fengling; Li, Xiaowen (Frontiers in Microbiology, 2024)
Introduction: Porcine viral diarrhea is a common clinical disease, which results in high mortality and economic losses in the pig industry. Porcine epidemic diarrhea virus (PEDV), porcine rotavirus (PoRV), and porcine deltacoronavirus (PDCoV) are important diarrhea viruses in pig herds. The similarities of their clinical symptoms and pathological changes make it difficult to distinguish these three viruses clinically. Therefore, there is a need for a highly sensitive and specific method to simultaneously detect and differentiate these viruses. Methods: A multiplex real-time PCR assay using TaqMan probes was developed to simultaneously detect PEDV, PoRV, and PDCoV. To assess the efficacy of the established assay, 30 clinical samples with diarrhea symptoms were used to compare the results obtained from the multiplex real-time PCR assay with those obtained from commercial singleplex real-time PCR kit. Importantly, a total of 4,800 diarrhea samples were tested and analyzed to validate the utility of the assay. Results: This multiplex real-time PCR assay showed high sensitivity, specificity, and excellent repeatability with a detection limit of 1×102 copies/μL. Comparing the results of the commercial singleplex real-time PCR kit and the multiplex real-time PCR method for detecting PEDV, PoRV, and PDCoV, there was complete agreement between the two approaches. Clinical data revealed single infection rates of 6.56% for PEDV, 21.69% for PoRV, and 6.65% for PDCoV. The co-infection rates were 11.83% for PEDV + PoRV, 0.29% for PEDV + PDCoV, 5.71% for PoRV + PDCoV, and 1.29% for PEDV + PDCoV + PoRV, respectively. Discussion: The multiplex real-time PCR method established in this study is a valuable diagnostic tool for simultaneously differentiating PEDV, PoRV, and PDCoV. This method is expected to significantly contribute to prevent and control the spread of infectious diseases, as well as aid in conducting epidemiological investigations.